Stakeholder Consultation on Using experiential learning methods & tools to strengthen community water management - Falk, Thomas; Meinzen-Dick, Ruth S.; Priyadarshini, Pratiti; Singh, Subrata; Mittal, Rajesh (2022)
Thomas Falk, Ruth Meinzen-Dick, Pratiti Priyadarshini, Subrata Singh, and Rajesh Mittal. 2022. Social Learning in Games: Stimulating institutional and Behavior Change in Relation to Water Use in India. PowerPoint presentation given during Stakeholder Consultation with Agriculture Department Bureaucrats from Odisha, Andhra Pradesh, Karnataka, Rajasthan, Maharashtra and Madhya Pradesh, India, 4pm IST, August 4, 2022 (virtual).